MEDIA RELATIONS STRATEGY IN MADIUN DISTRICT COMMUNICATION AND INFORMATICS DEPARTMENT IN SENDING GOVERNMENT PROGRAMS - Susi Yanti; Andhita Risko Faristiana (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2022)
The importance of media relations which is commonly used by several public relations in government has implications for government policies according to the information needs of the public. One of them is the Madiun Regency Communication and Information Service regarding the problems of socializing government programs. This study aims to describe the media relations of the Madiun District Communication and Information Service in optimizing the dissemination of Government work programs. The type of research used is descriptive qualitative. Through data collection techniques, namely interviews and documentation in the discussion of this study. The results of the study, the media relations of the Madiun Regency Communication and Information Service, namely managing relations, developing strategies, and developing networks. In implementing media relations, there are forms of media relations by the Madiun District Communication and Information Office, namely Press Conferences, Press Receptions, Press Briefings, Press Gatherings, Press Gatherings, and Press Tours